A retrospective, matched paired analysis comparing bendamustine containing BeEAM versus BEAM conditioning regimen: results from a single center experience. Issue 11 (2nd November 2018) - Saleh, Khalil; Danu, Alina; Koscielny, Serge; Legoupil, Clémence; Pilorge, Sylvain; Castilla-Llorente, Cristina; Ghez, David; Lazarovici, Julien; Michot, Jean-Marie; Khalife-Saleh, Nadine; Lapierre, Valerie; Alenxandrova, Kamelia; et al.
Abstract: The combination of carmustine, etoposide, aracytin, and melphalan(BEAM) conditioning regimen in autologous stem-cell transplantation (ASCT) is widely used in patients with relapsed/refractory non-Hodgkin lymphoma (NHL) and Hodgkin lymphoma. It is also an option in patients with very-high risk aggressive NHL in first complete remission (CR). Recently, a phase Ib–II feasibility study using bendamustine replacing carmustine (BCNU) was reported. We report herein a safety and efficacy analysis of bendamustine-EAM (BeEAM) with a control BEAM counterpart paired cohort (1/2). One hundred and two patients were analyzed. Overall survival (OS) and progression-free survival (PFS) were not reached and seemed to be comparable between both groups. However, grade III or greater diarrhea was significantly higher in BeEAM patients (44 vs. 15%, p = .002). The median number of days with fever >38 °C was significantly higher in BeEAM group (5.5 vs. 2, p < .001). This case-control study suggests that BeEAM followed by ASCT using bendamustine at 100 mg/m 2 /d is effective but has a different toxicity profile than the BEAM regimen.